Assessing the Performance of Dual-Frequency Multi-Constellation GBAS Architectures during Periods of Ionospheric Scintillation in Brazil - da Silva, Crislaine Menezes [UNESP]; da Costa Silva, Weverton [UNESP]; de Souza, Felipe Tintino Linhares [UNESP]; Francisco, João [UNESP]; Monico, Galera [UNESP]; Alves, Daniele Barroca Marra [UNESP]; Tsuchiya, Italo [UNESP]; Balvedi, Glaucia; Murphy, Tim; Saito, Susumu; Wichgers, Joel (Institute of Navigation, 2023)
A Ground-Based Augmentation System (GBAS) is a flight critical system that supports for safe, efficient, and essentially all-weather aircraft precision approach and landing operations. GBAS Approach Service Type (GAST)-X a proposed architecture candidate for future dual frequency multi-constellation (DFMC) GBAS, consisting of an uplink to the airborne that includes dual frequency raw measurements. The nominal mode of operation uses divergence-free (DFree) smoothing with up to 600 seconds of carrier smoothing, while ionosphere-free (IFree) and conventional single frequency (SF) smoothing are performed in parallel to support degraded/backup modes of operation. The use of DFree smoothed measurements makes the system less susceptible to ionospheric gradient threats. One of the benefits of GAST-X is the higher operational availability in equatorial areas due to the higher number of satellites in view offered by the multi-constellation services. In this study, the performance of different DFMC GBAS architectures was assessed using data from a set of five receivers located in Brazil, using GPS and Galileo data. The results showed that the protection levels calculated using the GAST-X architecture were better than those calculated using GAST F, which is an alternative architecture that uses SF 100-second smoothing as its primary mode of operation and with the second frequency being used for ionospheric gradient monitoring, demonstrating the robustness of the service, especially when using DFree smoothed pseudoranges. However, DFMC GBAS performance can degrade during conditions where cycle slips occur, and depending on the intensity of ionospheric scintillation, one or more backup modes can be more suitable than the nominal DFree mode of GAST-X or the single-frequency mode of GAST F.